2014
DOI: 10.2215/cjn.06620613
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Peritoneal Dialysis Patients

Abstract: Background and objective In the general population, metabolic syndrome (MES) is associated with cardiovascular risk. However, the definition of MES and its prognostic implication among patients undergoing peritoneal dialysis (PD) remain controversial.Design, setting, participants, & measurements We studied 329 prevalent PD patients from April 2008 to April 2011 and compared four sets of diagnostic criteria: the original World Health Organization (WHO) criteria, the International Diabetes Federation (IDF) crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
3
21
0
1
Order By: Relevance
“…A previous study also reported that visceral fat content, as measured by bioimpedance analysis, is a simple method for predicting the risk of chronic kidney disease and metabolic syndrome in the general population [23]. Since the primary objective of our study was to determine the prevalence and contributing factors of frailty, we did not perform extensive analysis on the possible clinical implications of central obesity in PD patients, which has been examined in detail in another study by our group [24].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also reported that visceral fat content, as measured by bioimpedance analysis, is a simple method for predicting the risk of chronic kidney disease and metabolic syndrome in the general population [23]. Since the primary objective of our study was to determine the prevalence and contributing factors of frailty, we did not perform extensive analysis on the possible clinical implications of central obesity in PD patients, which has been examined in detail in another study by our group [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the greater weight gain with PD compared with HD is unclear. 114,125,126 Again the role of treatment modality varies, as new-onset diabetes is less common in Chinese patients treated with PD than HD, and in either dialysis modality much less than for newly transplanted patients. However, in many circumstances this weight gain reflects catch-up of the predialysis loss.…”
Section: Cardiovascular Risk Modification In Pd Patientsmentioning
confidence: 99%
“…While some of the traditional risk factors for cardiovascular diseases, like DM and smoking, increased cardiovascular disease mortality in ESRD patients just like in the normal population, other traditional factors such as BMI, serum cholesterol and blood pressure showed a reverse epidemiology in long-term dialysis patients in that obesity, hypercholesterolemia and hypertension may appear to be protective features that are associated with a greater survival among dialysis patients [33,35]. Less data were available concerning Asian PD patients.…”
Section: Issues Related To Peritoneal Dialysis In Asian Countriesmentioning
confidence: 99%
“…However, different outcomes were observed in obese patients. Some reasons for the difference in outcomes in obese PD patients may be due to a different definition of obesity, variable duration of the study period, wide variability in patient characteristics in different studies and the fact that BMI is unable to distinguish between fat mass and muscle mass, which obviously affects survival outcomes [35]. …”
Section: Issues Related To Peritoneal Dialysis In Asian Countriesmentioning
confidence: 99%